Guidance System Design - Sadraey, Mohammad H (Design of Unmanned Aerial Systems, 2020)
A UAV – through guidance and control systems – must generate the steering commands and subsequent control surface deflections to adequately adjust its way along the chosen flight path. This chapter describes various aspects of guidance system, and elements of guidance system. There are various types of guidance laws. Four classical guidance laws for UAVs are: proportional navigation guidance; pursuit guidance; waypoint navigation guidance; and line‐of‐sight guidance (i.e., command guidance). The chapter depicts a graphical representation of three basic guidance laws by comparing the flight paths of a UAV that targets another vehicle. The selection of guidance law dictates the selection of hardware, and it influences the overall cost. Moreover, the type of guidance law will affect the control system, and navigation system. Thus, a systems engineering vision is required to select the best guidance law for a specific mission.